2011
DOI: 10.1111/j.1570-7458.2011.01123.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soil organisms on aboveground multitrophic interactions are consistent between plant genotypes mediating the interaction

Abstract: Belowground communities can affect interactions between plants and aboveground insect communities. Such belowground–aboveground interactions are known to depend on the composition of belowground communities, as well as on the plant species that mediates these interactions. However, it is largely unknown whether the effect of belowground communities on aboveground plant–insect interactions also depends on genotypic variation within the plant species that mediates the interaction. To assess whether the outcome o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 38 publications
0
17
1
Order By: Relevance
“…Similarly, it is unclear how the glucosinolate gluconapin, which was decreased by nematodes, affects aphid populations. Other studies that addressed effects of nematodes on leaf glucosinolates (Kabouw et al 2011; Kutyniok and Müller 2012; Lohmann et al 2009; Van Dam et al 2005; Wurst et al 2006) showed no clear pattern, but we can conclude that there was no increase in total glucosinolates after nematode infestation. In terms of specific glucosinolate classes, increases (Lohmann et al 2009), decreases (van Dam et al 2005; Wurst et al 2006), or no effects (Kutyniok and Müller 2012) have been found in aliphatic compounds.…”
Section: Discussioncontrasting
confidence: 54%
“…Similarly, it is unclear how the glucosinolate gluconapin, which was decreased by nematodes, affects aphid populations. Other studies that addressed effects of nematodes on leaf glucosinolates (Kabouw et al 2011; Kutyniok and Müller 2012; Lohmann et al 2009; Van Dam et al 2005; Wurst et al 2006) showed no clear pattern, but we can conclude that there was no increase in total glucosinolates after nematode infestation. In terms of specific glucosinolate classes, increases (Lohmann et al 2009), decreases (van Dam et al 2005; Wurst et al 2006), or no effects (Kutyniok and Müller 2012) have been found in aliphatic compounds.…”
Section: Discussioncontrasting
confidence: 54%
“…M. persicae also showed a reduced growth rate and fecundity when feeding on M. incognita -infected Nicotiana tabacum (Kaplan et al, 2011). In contrast, no effect on the performance of B. brassicae was found by an infection of B. oleracea with a mix of different root parasitic nematode species (Kabouw et al, 2011). In A. thaliana , a simultaneous inoculation with the sedentary endoparasitic nematode H. schachtii and the aphid B. brassicae was performed (Kutyniok and Muller, 2012).…”
Section: Aboveground–belowground Interactions Between Nematodes and Imentioning
confidence: 94%
“…A number of studies have shown that soil organisms such as root herbivorous insects, nematodes, and bacteria and fungi can affect the concentrations of primary and secondary compounds in aboveground plant tissues and subsequently the performance of aboveground herbivores (Bezemer et al 2005, Erb et al 2009, Eisenhauer et al 2010, Kabouw et al 2011, Johnson et al 2012, Soler et al 2012. Changes in soil nutrient availability can also influence plant nutritional quality (Koricheva et al 1998, Hol 2011.…”
mentioning
confidence: 99%